Observational Study of PD-L1, TGF-β, and Immune Cell Infiltrates in Hepatocellular Carcinoma - Ihling, Christian; Naughton, Bartholomew; Zhang, Yue; Rolfe, P. Alexander; Frick-Krieger, Eveline; Terracciano, Luigi M.; Dussault, Isabelle (Frontiers in Medicine, 2019)
Introduction: Hepatocellular carcinoma (HCC) typically develops in cirrhotic livers, with increased programed death ligand 1 (PD-L1) and transforming growth factor beta (TGF-β) activity implicated in immunosuppression. Methods: In an observational study of HCC liver samples, we determined the incidence of PD-L1 and immune cell (IC) infiltrates, and signs of TGF-β activity. HCCs were characterized by the incidence and distribution of PD-L1+ cells, and CD8+, CD68+, and FoxP3+ infiltrating ICs in HCC and surrounding liver. Gene expression signatures (GESs) associated with TGF-β activity and ICs were evaluated by RNAseq. Results: In non-neoplastic cirrhotic and non-cirrhotic liver, PD-L1 occurred on sinusoidal lining cells (mostly Kupffer cells), endothelial cells and ICs. In HCC, PD-L1+ tumor cells were rare. Most PD-L1+ cells were identified as ICs. CD8+, CD68+, and FoxP3+ ICs were associated with HCC, particularly in the invasive margin. CD8+ cell incidence correlated with PD-L1+ cells, consistent with PD-L1 being upregulated in response to pre-existing cytotoxic T-lymphocyte activity. TGFB1 mRNA levels and TGF-β activation GES correlated with the strength of the tumor-associated macrophage GES. Conclusion: Inhibition of PD-L1+ ICs and TGF-β activity and their respective immunomodulatory pathways may contribute to antitumor effects in HCC.